BUILDING ENVIRONMENTAL AWARENESS THROUGH RELIGIOUS TOURISM IN TANGKAHAN, LANGKAT REGENCY, NORTH SUMATRA PROVINCE - Wiharjokusumo, Padriadi; Girsang, Dameria; Saragih, Novita Romauli; Karo-Karo, Selamat (Jurnal Ilmiah Akomodasi Agung, 2024)
Religious tourism is a form of travel that not only offers spiritual experiences but also plays a significant role in enhancing environmental awareness among communities. This study aims to analyze the role of religious tourism in building environmental awareness in Tangkahan, Langkat Regency, North Sumatra Province. The research adopts a qualitative approach, with data collected through interviews, observations, and literature reviews. The findings reveal that religious tourism in Tangkahan has successfully raised higher awareness among tourists and local communities regarding environmental issues. Activities such as waste management, flora and fauna conservation, and environmental education integrated into religious tourism programs have effectively increased community participation in preserving the environment. Furthermore, the study found that the sustainable utilization of natural resources in religious tourism activities not only provides economic benefits to the community but also protects the environment. The conclusion of this research suggests that religious tourism in Tangkahan can serve as an effective means of fostering environmental awareness and could be used as a model for other regions to develop environmentally friendly tourism. The study offers recommendations for the development of more intensive environmental education programs and collaboration between the government, tourism operators, and local communities.